Why is everybody yelling? : growing up in my immigrant family - Russo, Marisabina (Farrar Straus Giroux, 2021)
An illustrated autobiography of Marisabina "Cookie" Russo, speaking to her childhood and teen years growing up in the 1950s and 1960s with a distant, mostly disapproving father and a highly opinionated mother. When she finds out her family is Jewish survivors of the Holocaust, she finds her whole world thrown into turmoil. "Cookie" must find a way to make a life for her own and find her own voice and beliefs in life.